Hey everyone,
I am currently facing a algebra question which have stumped me for days.
I try numerously but I was told that the way I done was wrong.
Can you guys lend me a hand?
I need to make
1) �� the subject in the equation for the first question.
2) �� the subject in the equation for the second question.
Both of the question uses the same equation
b = −(10��������10��+ a)
The questions are done seperately.
b= -(10 n log_10(d)+ a)= -10 n log_10(d)- a
Add a to both sides:
a+ b= -10 n log_10(d)
To solve for n, since -10log_10(d) is multiplied by it, divide both sides by those:
-(a+ b)/(10 log_10(d))= n
Going back to a+ b= -10 n log_10(d), to solve for d, first solve for log_10(d) by dividing both sides by -10 n to get
-(a+ b)/(10 n)= log_10(d)
and then "reverse" the logarithm by using its inverse function 10 to the power:
10^(-(a+b)/(10 n))= d